Zasiłki pogrzebowe i inne świadczenia na pokrycie kosztów pogrzebu i upamiętnienia osoby zmarłej - Lewandowicz-Machnikowska, Monika (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The consequence of the death of a man is the need to bury their body. To exercise their right to burial of the deceased, members of the family must have the ability to incur substantial costs associated with the burial rite. The paper discusses the funeral allowance and other benefits to cover funeral costs and to commemorate the deceased
Keywords: funeral allowance; burial; funeral expenses; funerals; social benefits